The Impact of Cumulative Cochlear Implant Wear Time on Spoken Language Outcomes at Age 3 Years. - Gagnon, Erika B.; Eskridge, Hannah; Brown, Kevin D.; Park, Lisa R. (Journal of Speech, Language & Hearing Research, 2021)
Purpose: The purpose of this study was to analyze the impact of cumulative hearing hour percentage (HHP) on pediatric cochlear implant users’ speech and language development at age 3 years and to determine an evidencebased wear time recommendation that yields typical spoken language standard scores. Method: A retrospective chart review of 40 pediatric cochlear implant recipients was completed. Children met the following criteria: prelingually deafened, implanted at age 2 years or younger, utilized a speech processor with datalogging capabilities, a minimum of 1 year of cochlear implant use, and language testing completed at approximately age 3 years. Exclusion criteria included significant inner ear malformation (i.e., common cavity) or developmental delay that would preclude spoken language development. Results: Multiple regression analysis revealed that age and implantation and HHP were predictive of spoken language skills at age 3 years. Further analysis yielded wear time recommendations associated with age-appropriate spoken language based on the age at implantation. Conclusions: When the goal is age-appropriate spoken language, wear time recommendations should reflect a child’s current age, age at implantation, and the comparative daily sound access of age-matched normal-hearing peers. The HHP measurement can help provide that information. The minimum wear time recommendation should be set to 80% HHP with the ultimate goal of 100% HHP to give pediatric cochlear implant recipients enough access to sound and language to achieve their spoken language goals.